366. Characteristics and Outcomes of COVID-19 Patients with Fungal Infections. (31st December 2020) - Herc, Erica; Yared, Nicholas F; Kudirka, Adam; Suleyman, Geehan
Abstract: Background: There is concern that patients with coronavirus disease 2019 (COVID-19) are at risk of developing secondary bacterial and fungal infections; however, data on the clinical characteristics and outcomes of COVID-19 patients with fungal infections are limited. We evaluated the risk factors and mortality of hospitalized COVID-19 patients with fungal infections. Methods: This was a retrospective chart review of 51 patients with fungal infections at an 877-bed teaching hospital in Detroit, Michigan from March through May 2020. Demographic data, comorbidities, complications, treatment, and outcomes, including relapse, readmission and mortality were collected. We performed a descriptive analysis. Results: A total of 51 patients with fungal infections were included, in which 31 (60.8%) had confirmed or suspected COVID-19 infection. Of the COVID-19 patients, the average age was 66 years and the majority (54.9%) were female. The average length of stay (LOS) was 29.3 days. Aspergillus sp. (2 A. fumigatus, 1 A. niger ) were isolated in 3 (10%) patients while 23 (74.2%) had candidemia diagnosed via blood culture or T2Candida® Panel. One had a positive serum galactomannan. The average time from admission to diagnosis was 13 days. Significant comorbidities included hypertension (74%), diabetes (51.6%), coronary artery disease (25.8%), congestive heart failure (32.2%), chronic kidney disease (22.6%), and malignancy (16.1%). Most patients received steroids (83.9%) and broad-spectrum antibiotics (80.6%), had a central line (80.6%), and required intensive care unit management (90%). Only 71% were treated with antifungals. One patient with candidemia relapsed due to poor source control; two were readmitted within 30 days. In-hospital mortality rate was 51.6% among COVID-19 patients. Conclusion: COVID-19 patients with fungal infections had multiple comorbidities, prolonged hospitalization and predisposing risk factors for fungal infections with a high in-hospital mortality rate. Prevention of fungal infections in COVID-19 patients is paramount. Disclosures: All Authors : No reported disclosures